ANTI-INFLAMMATORY EFFECTS OF NESFATIN-1 IN RATS WITH ACETIC ACID - INDUCED COLITIS AND UNDERLYING MECHANISMS - (:unkn) unknown (POLISH PHYSIOLOGICAL SOC, 2015)
Mucosal balance impairment, bacterial over-proliferation, cytokines, inflammatory mediators are known as responsible for inflammatory bowel disease. Besides known anorexigenic, neuroprotective, and anti-apoptotic effects, the major effect of nesfatin-1 on colitis is unknown. Our aim was to investigate the possible anti-inflammatory effects of nesfatin-1 in acetic acid induced colitis model and potential underlying mechanisms. Male Spraque-Dawley rats were anesthetized by intraperitoneal ketamine (100 mg/kg) and chlorpromazine (0.75 mg/kg). For nesfatin-1 and antagonist applications some of the rats were intracerebroventricularly (i.c.v.) cannulated. In colitis group, intrarectally (i.r.) 4% acetic acid solution (1 ml) and 10 minutes later i.c.v. nesfatin-1 (0.05 mu g/5 mu l) or vehicle (5 mu l) were administered. Treatments continued for 3 days. In control group, physiological saline solution was used intrarectally. To identify the underlying effective mechanism of nesfatin-1, rats were divided into 3 subgroups, 5 minutes following colitis induction; i.c.v. atosiban (oxytocin receptor antagonist), SHU9119 (melanocortin receptor antagonist) or GHSR-1a antagonist (ghrelin receptor antagonist) were administered, 5 minutes later nesfatin-1 was administered for 3 days. On the fourth day, rats were decapitated, and colon tissues were sampled. Macroscopic and microscopic damage scores of distal colon, and colonic tissue malondialdehyde, glutathione, myeloperoxidase, superoxide dismutase, catalase, luminol and lucigenin chemiluminescence measurements were analysed. The increased myeloperoxidase activity, malondialdehyde levels, luminol and lucigenin chemiluminescence measurements, macroscopic and microscopic damage scores with colitis induction (P < 0.05 - 0.001) were decreased with nesfatin-1 treatment (P < 0.05 - 0.001). Nesfatin-1 may show this effect by inhibiting neutrophil infiltration through tissues and by decreasing formation of free oxygen radicals. Atosiban and GHSR-la administration alleviated the protective effect of nesfatin-1 from microscopic and oxidant damage parameters and lipid peroxidation (P < 0.05 - 0.001). The results of the study suggest that nesfatin-1 had a protective effect from colitis induction, and the anti-inflammatory and antioxidant effects of nesfatin-1 on colitis might occur via oxytocin and ghrelin receptors.
Keywords: nesfatin-1; acetic acid-induced colitis; ghrelin receptor; oxytocin receptor; melanocortin receptor; lipid peroxidation; myeloperoxidase; INDUCED ULCERATIVE-COLITIS; SUPEROXIDE-DISMUTASE; GASTRIC DAMAGE; GHRELIN; INFLAMMATION; OXYTOCIN; BRAIN; RECEPTOR; NEURONS; CHOLECYSTOKININ